Pengaruh Citra Merek Terhadap Keputusan Pembelian Pakan Hewan Pada Konsumen Toko Pet Shop - Didit Darmawan; Naila Septiana Camelia (Pelantar Press, 2026)
The pet food industry in Indonesia, particularly the cat food category, has experienced rapid growth in line with increasing public awareness of pet welfare. The increasingly intense market conditions and competitive dynamics have compelled business managers to formulate more comprehensive marketing strategies, with a focus on strengthening brand image. This study focuses on understanding how brand image influences consumers’ decisions to purchase pet food products. A qualitative approach based on library research was applied in this study through the synthesis of data from various accredited academic literature sources, analyzed using descriptive methods. The results indicate that brand image significantly influences purchasing decisions for pet food products. A strong brand image enhances trust, shapes perceptions of quality, and reduces consumer uncertainty, thereby driving purchasing decisions. However, this influence is not isolated but is shaped by interactions with other factors such as promotions, price perceptions, product quality, and service quality. The conclusion of this study emphasizes that brand image is a strategic factor in purchasing decisions; therefore, it needs to be strengthened through a holistic marketing approach to enhance trust and drive sustainable purchases